Development of BP-based seismic behavior optimization of RC and steel frame structures. (1st June 2018) - Xu, Long-He; Yan, Xin-Tong; Li, Zhong-Xian
Highlights: Seismic performance optimization method of structure based on BP algorithm is proposed. Seismic sensitive components are identified by modifying weighting coefficients. Experimental validation of mechanical model of SCED brace is carried out. BP-based optimization can effective improve seismic performance of RC and steel frames. Abstract: The present study develops and numerically verifies a new methodology for the seismic behavior enhancement of reinforced concrete (RC) and steel frames incorporating BP (Back Propagation) algorithm and performance-based estimation. The proposed optimization flow allows automatic correction of the assumed damage weighting coefficients of the components with a series of prepared local and global damage indices defined as required. On the basis of the revised coefficients, modification of the sectional dimensions and corresponding reinforcement ratio of a six-story RC frame is carried out. The exceeding probability of each limit state and the Mean Annual Frequency (MAF) are reduced, leading to a better safety margin of the RC structure. And the mechanical model of a user defined element of self-centering energy dissipation brace (SCEDB) is experimentally confirmed. Meanwhile, the installation strategy against the normal continuous arrangement of the SCEDBs in a nine-story benchmark steel frame is proposed as well. As a result, the story drift ratio and local damage of the steel frame are effectively decreased. The BP-based optimization results demonstrate that the seismic performance of the two structures has been improved without any cost increase, resulting in an effective structural optimization method.